2016
DOI: 10.1364/optica.3.000339
|View full text |Cite
|
Sign up to set email alerts
|

Role of epsilon-near-zero substrates in the optical response of plasmonic antennas

Abstract: Radiation patterns and the resonance wavelength of a plasmonic antenna are significantly influenced by its local environment, particularly its substrate. Here, we experimentally explore the role of dispersive substrates, such as aluminum-or gallium-doped zinc oxide in the near infrared and 4H-silicon carbide in the mid-infrared, upon Au plasmonic antennas, extending from dielectric to metal-like regimes, crossing through epsilon-near-zero (ENZ) conditions. We demonstrate that the vanishing index of refraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
119
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(125 citation statements)
references
References 52 publications
4
119
0
Order By: Relevance
“…We note that when the ENZ medium is sufficiently thick, the antenna resonance gets locked to the zero permittivity wavelength of the ENZ material [37]. Nevertheless a metasurface that incorporates a thick ENZ material will also exhibit enhanced nonlinear response because a dynamic change in the substrate's refractive index necessarily modifies the resonance wavelength of the antenna.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…We note that when the ENZ medium is sufficiently thick, the antenna resonance gets locked to the zero permittivity wavelength of the ENZ material [37]. Nevertheless a metasurface that incorporates a thick ENZ material will also exhibit enhanced nonlinear response because a dynamic change in the substrate's refractive index necessarily modifies the resonance wavelength of the antenna.…”
mentioning
confidence: 90%
“…Thus, ENZ material with lower intrinsic damping could increase the saturation threshold. The nonlinear response could be further enhanced by maximizing the overlap between the near-field of the antennas and the ITO layer, by choosing antennas (dielectric or metallic) with higher quality factors, and by choosing an ENZ material with lower intrinsic damping [18,36] .We note that when the ENZ medium is sufficiently thick, the antenna resonance gets locked to the zero permittivity wavelength of the ENZ material [37]. Nevertheless a metasurface that incorporates a thick ENZ material will also exhibit enhanced nonlinear response because a dynamic change in the substrate's refractive index necessarily modifies the resonance wavelength of the antenna.…”
mentioning
confidence: 97%
“…When the area of the single‐zero ZIM approaches zero, the results would be the same as those obtained for doped DZIM. We note that single‐zero ZIM like ENZ media have the advantage of easy fabrication in the optical regime by using conductive materials with Drude or Drude‐like dispersions, such as doped semiconductors, indium tin oxide, aluminum‐doped zinc oxide, etc.…”
Section: Versatile Mechanisms For Absorption Controlmentioning
confidence: 99%
“…In this work, by utilizing the unique constraint of constant fields within zero‐index medium (ZIM, with permittivity or/and permeability near zero), we propose to realize CPA via the photonic doping of ZIM with absorptive defects. The concept and theory of “photonic doping” of an epsilon‐near‐zero (ENZ) medium, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In recent years, optical antennas have attracted considerable interest and hold promise to improve the performance in a large number of applications, such as near-field scanning optical microscopy, 5 photo-detectors, 6 photovoltaic cells, 7 thermal emitters, 8 saturable absorbers, 9 upconverted incoherent nonlinear emission, 10,11 single-molecule fluorescence enhancement, 12 and third harmonic generation (THG) enhancement. 13 Due to the lightning-rod effect and the coupling of two metal nanotriangles (coupled plasmons), it has been shown that bowtie nanoantennas 14 can achieve stronger intensity enhancement than other comparable structures such as rod-, ellipse-, disk-, and cross-shaped nanoantennas.…”
mentioning
confidence: 99%